Polydopamine deposition with anodic oxidation for better connective tissue attachment to transmucosal implants. (24th October 2017) - Teng, F.; Chen, H.; Xu, Y.; Liu, Y.; Ou, G.
Abstract : Background and Objective: Nowadays, most designs for the transmucosal surface of implants are machined‐smooth. However, connective tissue adhered to the smooth surface of an implant has poor mechanical resistance, which can render separation of tissue from the implant interface and induce epithelial downgrowth. Modification of the transmucosal surface of implants, which can help form a good seal of connective tissue, is therefore desired. We hypothesized that anodic oxidation (AO) and polydopamine (PD) deposition could be used to enhance the attachment between an implant and peri‐implant connective tissue. We tested this hypothesis in the mandibles of Beagle dogs. Material and Methods: AO and PD were used to modify the transmucosal region of transmucosal implants (implant neck). The surface microstructure, surface roughness and elemental composition were investigated in vitro. L929 mouse fibroblasts were cultured to test the effect of PD on cell adhesion. Six Beagle dogs were used for the in vivo experiment (n = 6 dogs per group). Three months after building the edentulous animal model, four groups of implants (control, AO, PD and AO + PD) were inserted. After 4 months of healing, samples were harvested for histometric analyses. Results: The surfaces of anodized implant necks were overlaid with densely distributed pores, 2–7 μm in size. On the PD‐modified surfaces, N1s, the chemical bond of nitrogen in PD, was detected using X‐ray photoelectron spectroscopy. L929 developed pseudopods more quickly on the PD‐modified surfaces than on the surfaces of the control group. The in vivo experiment showed a longer connective tissue seal and a more coronally located peri‐implant soft‐tissue attachment in the AO + PD group than in the control group ( P  < .05). Conclusion: The modification of AO + PD on the implant neck yielded better attachment between the implant and peri‐implant connective tissue.